2022
DOI: 10.1186/s12886-022-02663-w
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface disorders affect quality of life in patients with autoimmune blistering skin diseases: a cross-sectional study

Abstract: Background Autoimmune blistering skin diseases (AIBD) are a group of rare chronic autoimmune diseases which are associated with ocular surface diseases especially dry eye disease. This study is designed to investigate the relationship between ocular surface disorders and quality of life among patients with autoimmune blistering skin diseases. Methods Twenty-four AIBD patients (18 pemphigus and 7 pemphigoid) and twenty-five non-AIBD controls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Insufficient sleep can cause various diseases, such as diabetes, obesity, and vascular diseases [ 3 ]. In the eye, previous studies have reported that sleep deprivation (SD) is a major risk factor for ocular surface diseases, such as dry eye and corneal epithelial lesions [ 4 7 ]. Therefore, the harm of sleep loss on ocular health has drawn the attention of ophthalmologists.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient sleep can cause various diseases, such as diabetes, obesity, and vascular diseases [ 3 ]. In the eye, previous studies have reported that sleep deprivation (SD) is a major risk factor for ocular surface diseases, such as dry eye and corneal epithelial lesions [ 4 7 ]. Therefore, the harm of sleep loss on ocular health has drawn the attention of ophthalmologists.…”
Section: Introductionmentioning
confidence: 99%
“…These lesions can have important extra-oral complications, one of the most important of which is eye involvement, which can even lead to blindness. The vesiculobullous diseases previously mentioned can cause a variety of symptoms in the eye, from mild irritation and dry eye to severe vision loss, symblepharon, eyelid malposition, chronic conjunctivitis, and ocular surface scarring ( Kang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%